Development of a hybrid hydrogel for submucosal injection in endoscopic resection of gastrointestinal neoplasm: From laboratory to clinical trial - Kang, Jui-Wen; Chen, Po-Jun; Chen, Chiung-Yu; Riley, Guillermo; Wang, Yao-Sheng; Kuo, Hsin-Yu; Chuang, Chiao-Hsiung (Endoscopy International Open, 2023)
Background and study aims Submucosal injection solution is essential for successful endoscopic resection of the early gastrointestinal tumor. We evaluated a new endoscopic hydrogel for submucosal injection and its clinical feasibility.Patients and methods A hydrogel (AceGel) containing 0.4% sodium alginate and 2% calcium lactate was developed for ex vivo and animal studies. Subsequently, a prospective, single-arm study was conducted to assess its feasibility and safety in humans. Patients with gastrointestinal neoplasms undergoing endoscopic resection were enrolled. All patients underwent endoscopic surveillance after 4 weeks and outpatient follow-up at week 6. Afterward, they received endoscopic follow-up according to the medical routine.Results In the ex vivo experiments, the submucosal elevation height of AceGel was equivalent to sodium hyaluronate and superior to saline or glycerol. Animal studies showed that the excised wounds healed well without surrounding tissue damage. Twelve patients participated in the clinical trial, including three, two, and seven patients with esophageal, gastric, and colonic lesions, respectively. The mean neoplasm size and submucosal injection volumes were 24.0±8.6 mm and 22.8±19.9 mL, respectively. All patients had adequate wound healing on 4-week surveillance endoscopy, and none had serious adverse events during 6-week follow-up. Moreover, endoscopic follow-up showed complete wound healing after 6 to 46 months without local mucosal inflammation in all patients.Conclusions AceGel is good for endoscopic submucosal injection and demonstrated its usefulness in durable mucosal elevation for endoscopic therapy in preclinical tests. This clinical trial shows its safety and feasibility in all participating patients.
Keywords: endoscopic submucosal injection; endoscopic submucosal dissection; endoscopic mucosal resection